Anti-Inflammatory and Antioxidant Effect of Eucommia ulmoides Polysaccharide in Hepatic Ischemia-Reperfusion Injury by Regulating ROS and the TLR-4-NF-κB Pathway. (27th May 2020) - Gao, Weidong; Feng, Zanjie; Zhang, Shilong; Wu, Bo; Geng, Xin; Fan, Guoxin; Duan, Yuling; Li, Kai; Liu, Kangwei; Peng, Cijun
Abstract : Eucommia ulmoides polysaccharide (EUP) has been shown to have anti-inflammatory and antioxidant effects. However, the mechanism underlying these effects has rarely been reported, and whether EUP can reduce liver injury in hepatic ischemia-reperfusion injury (HIRI) has not been reported. In this study, 40 Sprague-Dawley (SD) rats were randomly divided into 5 groups: the sham group, ischemia-reperfusion (I/R) group, and three EUP pretreatment groups (320 mg/kg, 160 mg/kg, and 80 mg/kg). SD rats were pretreated with EUP by gavage once a day prior to I/R injury for 10 days. Except for the sham group, blood flow in the middle and left liver lobes was blocked in all the other groups, resulting in 70% liver ischemia, and the ischemia and reperfusion times were 1 h and 4 h, respectively. Ischemic liver tissue and serum were obtained to detect biochemical markers and liver histopathological damage. Compared with the I/R group, after EUP pretreatment, serum alanine aminotransferase, aspartate aminotransferase, tumor necrosis factor- α, and interleukin-1 β levels were significantly decreased, malondialdehyde levels in liver tissues were significantly decreased, superoxide dismutase levels were significantly increased, and the area of liver necrosis was notably reduced. To understand the specific mechanism involved, we determined the levels of Toll-like receptor- (TLR-) 4-nuclear factor-kappaB (NF- κ B) pathway-associated proteins in vivo and in vitro. The data showed that EUP can reduce liver damage by decreasing ROS levels and inhibiting TLR-4-NF- κ B pathway activation and may be a promising drug in liver surgery to prevent HIRI.